CREATIVITY IN LIFE AND IN ART - Shodiya Mamadyorova,A. Abdulalilov (International Journal of Literature and Language Studies, 2026)
This article examines the importance of childhood in shaping a person's personality and developing their talents and abilities. It also discusses the role of theater, a distinct art form, in addressing the challenges of individuals and society.